PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI PENERAPAN MEDIA GAMBAR BERSERI PADA SISWA KELAS VIII - Yuni Khotimah; Rahutami; Suryantoro (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to describe the improvement of poetry writing skills through learning media applied in Indonesian language learning in the material of writing poetry in class VIII F SMP Negeri 12 Malang. This research is a type of Classroom Action Research (PTK) with a qualitative descriptive approach. The subjects of this study were students of class VIII-F SMP Negeri 12 Malang. Sources of data in this study are observation sheets of students and teachers, questionnaires, interviews, pre-tests, post-tests, and results/products. Data collection techniques in this research are observation, interview, questionnaire, and test. The results of this study show the process of improving the ability to write poetry in class VII-F SMP Negri 12 Malang can be seen from the evaluation results which show significant developments in the ability of students to write poetry. Based on the results of the research that has been done, it can be concluded that the application of serialized images has proven effective in improving the ability of students in writing poetry. This is shown in the increase in the value of students from cycle 1 to cycle 2. The completeness value of learning outcomes in writing poetry in cycle 1 averaged 72, while the average in cycle 2 rose to 86. The use of serial image media can be applied in learning to write poetry. In addition to pictures and sample sheets of poetry text, the use of these media is recommended to provide examples of the application of the media.